The Determinants of New-firm Survival across Regional Economies - Zoltán J. Ács; Catherine Armington; Ting Zhang (Max Planck Institute of Economics, 2006)
The process of the entrepreneurial decision is decomposed in seven engagement levels ranging from never thought about starting a business to gave up, thinking about it, taking steps for starting up, having a young business, having an older business and no longer being an entrepreneur. By using a multinomial logit model we allow the effect of covariates to differ across the various entrepreneurial engagement levels. Data from two Entrepreneurship Flash Eurobarometer surveys (2002 and 2003) con-taining over 20,000 observations of the 15 old EU member states, Norway, Iceland, Liechtenstein and the US are used. Other than demographic variables, the set of explanatory variables used includes the percep-tion by respondents of administrative complexities, of availability of financial support and of risk tolerance, the respondents preference for self-employment and country specific effects. Among our results we find that the perception of lack of financial support has no discriminative effect across the various levels of en-trepreneurial engagement while perception of administrative complexities plays a negative role only for high levels of engagement.
Keywords: H10; J23; L26; M13; R12; 330; entrepreneurship; determinants; nascent entrepreneurship; multinomial logit; barriers to entry; Europe; Unternehmensgründung; Unternehmensentwicklung; Region; Humankapital; Regionaler Arbeitsmarkt; USA